2015
DOI: 10.1038/cr.2015.126
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-scale detection of hypermethylated CpG islands in circulating cell-free DNA of hepatocellular carcinoma patients

Abstract: Despite advances in DNA methylome analyses of cells and tissues, current techniques for genome-scale profiling of DNA methylation in circulating cell-free DNA (ccfDNA) remain limited. Here we describe a methylated CpG tandems amplification and sequencing (MCTA-Seq) method that can detect thousands of hypermethylated CpG islands simultaneously in ccfDNA. This highly sensitive technique can work with genomic DNA as little as 7.5 pg, which is equivalent to 2.5 copies of the haploid genome. We have analyzed a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(92 citation statements)
references
References 23 publications
4
85
0
Order By: Relevance
“…Several studies revealed that promoter hypermethylation induced downregulation of miRNAs closely correlates with carcinogenesis [42]. Our data demonstrated that hypermethylation of upstream of miR-129-2 led to the downregulation of miR-129-2 in both HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…Several studies revealed that promoter hypermethylation induced downregulation of miRNAs closely correlates with carcinogenesis [42]. Our data demonstrated that hypermethylation of upstream of miR-129-2 led to the downregulation of miR-129-2 in both HCC tissues and cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…Given ctDNA is fragmented and accounts for only a small portion of cfDNA, this sensitive method is suitable for detecting ctDNA methylation, since it only requires small amounts of ctDNA (as low as 7.5 pg) [173]. This is the first genome-wide technique developed for the detection of ctDNA methylations (Table 4).…”
Section: Methods For Detecting Ctdnasmentioning
confidence: 99%
“…VIM methylation has been found to be more frequent in bladder urothelial carcinoma and UTUC, but rare in normal tissue, and may therefore be useful as a novel diagnosis and detection method in urothelial cancer. Downregulation of VIM has also been associated with increased tumor invasion, progression, epithelial to mesenchymal transition (EMT) and poor prognosis in various types of tumor (30)(31)(32)(33)(34). Monteiro-Reis et al (31) suggested that during early upper urinary tract carcinogenesis, the VIM promoter is progressively methylated and the gene is kept silenced, as in normal urothelium; by contrast, in a subset of UTUCs, methylation is decreased, allowing for aberrant vimentin expression, due to stimuli leading to EMT.…”
Section: Discussionmentioning
confidence: 99%